VIOLÊNCIA ASSOCIADA AO GÊNERO FEMININO NA BAIXADA MARANHENSE: ANÁLISE DOS CASOS NOTIFICADOS ENTRE 2013 A 2023 (REMUNOM, 2025)
Introduction: Gender-based violence, especially that perpetrated against women, constitutes a serious violation of human rights. This violence consists of any gender-based violent act that results in or is likely to result in physical, sexual, or psychological harm or suffering to women, including coercion or arbitrary deprivation of liberty in a public or private setting. General objective: To analyze the profile of victims of gender-based violence in Baixada Maranhense. Methodology: This is a cross-sectional study of an exploratory and descriptive nature using data from the Notification/Investigation of Interpersonal and Self-Inflicted Violence forms registered in (SINAN). The sample consisted of women residing in Baixada Maranhense, victims of gender-based violence between 2013 and 2023. Results: 1,072 cases of violence against women were reported in Baixada Maranhense from 2013 to 2023, with the highest number of records in 2020, especially in the municipality of Pinheiro-MA. Sexual violence was the most prevalent, accounting for 610 cases (56.9%), followed by physical violence, with 398 cases (37.1%). Regarding the profile of the victims, the most affected age group was adolescents between 10 and 19 years old, with 660 cases (61%). In addition, 282 women (26.3%) had incomplete elementary education and 808 (75%) declared themselves to be brown. Conclusion: This study contributes significantly by exploring sociodemographic factors associated with gender violence, providing important data that contribute to the creation of more assertive public policies